2016
DOI: 10.1139/cjas-2016-0143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of validated and population-specific single nucleotide polymorphism parentage panels in pedigreed and commercial beef cattle populations

Abstract: A pedigreed population containing 71 calves and 8 sires was used to compare sire qualification using three genotyping platforms [14 microsatellite, real-time quantitative PCR, and 100, 200, 500, and 1000 single nucleotide polymorphism (SNP) arrays]. Parentage was also qualified in an unknown-pedigree population containing 8480 calves with 460 sires using SNP arrays. The three platforms qualified the true sire in the known-pedigree population with zero mismatches. The 100 and 200 SNP arrays yielded specificitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A parent–offspring assignment was made whenever the number of opposing homozygotes was less than 1% of the number of markers in the assay. Setting such a threshold for identifying parent–offspring pairs was previously used [ 38 , 42 , 43 ] as a compromise to minimize false rejection or false assignment of parentages when the number of SNPs is small.…”
Section: Methodsmentioning
confidence: 99%
“…A parent–offspring assignment was made whenever the number of opposing homozygotes was less than 1% of the number of markers in the assay. Setting such a threshold for identifying parent–offspring pairs was previously used [ 38 , 42 , 43 ] as a compromise to minimize false rejection or false assignment of parentages when the number of SNPs is small.…”
Section: Methodsmentioning
confidence: 99%
“…Fernández et al [ 23 ] suggested that 2–3 SNPs are needed to obtain an equivalent exclusion power to one microsatellite, yet Gill et al [ 24 ] estimated that 4–5 SNPs with allele frequencies range from 0.2 to 0.8 give the same power of exclusion as for one microsatellite. Albeit the continuous attention to this issue, most of the research focused on SNP-PCR, SNP-chip or other approaches which conduct sequencing by NGS and genotyping SNPs via highly multiplexed laboratory assays [ 22 , 25 , 26 , 27 , 28 , 29 ], while few related reports have genotyped and filtered SNPs directly via bioinformatic pipeline based on NGS approaches such as genotyping-by-sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes were also used to pair sires with their progeny from a subset of available SNP markers ( McClure et al, 2015 ; Strucken et al, 2016 ; Buchanan et al, 2016a ). For the CM calves, sires were identified using a 1,000 SNP subset of the available marker panel and the SEEKPARENTF90 software to generate CM pedigree records ( Aguilar et al, 2014 ; Buchanan et al, 2016a ). For PB animals, historical 4-generation pedigree information was available containing 9,176 records.…”
Section: Methodsmentioning
confidence: 99%